Overlap among College and University Library Collections. Issue 3 (2nd July 2016) - Shaw, Debora
ABSTRACT: Analysis of twenty-six college and university libraries' monographic holdings in WorldCat shows that university libraries hold radically more rare titles and their collections are seven times larger than college libraries. Language and Literature (Library of Congress [LC] class P) accounts for 30% of university and 27% of college holdings. The number of books held declines and the number owned by only one library increases after the 2000 publication year. Since then, total library budgets have barely kept pace with inflation and book budgets have declined as a percentage of library expenditures. These changes align with current emphasis on priorities other than book collections.